Involvement of the mouth and jaw area in dermatological diseases - Ramiah, Vasudevi; Sankar, Shenbaga Lalitha; Shunmugavelu, Karthik; Hussain, Sajid Tajamul; Sadasivam, Manju Palanisamy; Behura, Shyam Sundar (GMS Hygiene and Infection Control, 2025)
Background: The oral cavity can be affected by a variety of disorders, and many systemic disorders have wide range of manifestations in the oral cavity. Oral mucosal lesions can be early manifestations of the disease or the only symptom of dermatological diseases; therefore no symptom or sign in the oral cavity should be neglected. Materials and methods: 1,131 patients who came to the Oral and Maxillofacial Pathology department for various dermatological treatments were included. The demographic details were obtained from each patient and a thorough dermatological examination was done. On examining the oral cavity, the size and the site of any lesions were noted. The results were entered in SPSS version 21 and descriptive statistics calculated (p<0.05 was considered statistically significant). Results: Out of 1,131 patients, 237 patients had both with dermatological and oral mucosal lesions. Psoriasis (44.3%) was most frequently accompanied by lesions of the oral mucosa, followed by pemphigus (31.2%) and bullous pemphigoid (10.1%). The most common site of involvement in the oral cavity was the palate (38.3%). Patients in the age group of 25–50 years (76%) were affected more than the other age groups. Male (49.7%) and female (50.3%) patients were equally affected. Conclusion: Diagnosing oral lesions in dermatology practice and mucocutaneous lesions in dental practice can play a pivotal role in patient management. Thus, comprehensive knowledge is necessary to diagnose these cases in dental and dermatology practice.